2022
DOI: 10.1038/s41467-022-33547-8
|View full text |Cite
|
Sign up to set email alerts
|

INTS13 variants causing a recessive developmental ciliopathy disrupt assembly of the Integrator complex

Abstract: Oral-facial-digital (OFD) syndromes are a heterogeneous group of congenital disorders characterized by malformations of the face and oral cavity, and digit anomalies. Mutations within 12 cilia-related genes have been identified that cause several types of OFD, suggesting that OFDs constitute a subgroup of developmental ciliopathies. Through homozygosity mapping and exome sequencing of two families with variable OFD type 2, we identified distinct germline variants in INTS13, a subunit of the Integrator complex.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 76 publications
2
25
0
Order By: Relevance
“…Meanwhile, the loss of the INTAC auxiliary module had a minimal effect on snRNA processing, corroborating prior studies. [71][72][73][74] Furthermore, our data showed that the INTAC auxiliary module did not influence the phosphatase activity of INTAC, aligning with structural analyses showing the auxiliary and phosphatase modules are located on opposite ends of the complex. 88,89 These observations imply that while the auxiliary module can integrate with INTAC and support the functioning of other modules in specific developmental contexts, [71][72][73][74] it likely holds independent roles beyond the two catalytic activities of the complex.…”
Section: Discussionsupporting
confidence: 86%
“…Meanwhile, the loss of the INTAC auxiliary module had a minimal effect on snRNA processing, corroborating prior studies. [71][72][73][74] Furthermore, our data showed that the INTAC auxiliary module did not influence the phosphatase activity of INTAC, aligning with structural analyses showing the auxiliary and phosphatase modules are located on opposite ends of the complex. 88,89 These observations imply that while the auxiliary module can integrate with INTAC and support the functioning of other modules in specific developmental contexts, [71][72][73][74] it likely holds independent roles beyond the two catalytic activities of the complex.…”
Section: Discussionsupporting
confidence: 86%
“…Beyond csr-1 , the genome-wide RNAi screen presented in this study has also identified several yet to be characterized regulators of snRNA processing including those encoding nuclear protein complex. Given the expansion of a broad role for the Integrator complex in gene expression control beyond snRNA processing, and its emerging implication in human diseases [8,14], it will ultimately be of interest to determine whether these novel regulators may also influence snRNA independent function of the Integrator in contributing to transcriptome stability.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypically, human mutations to the Integrator complex have been linked to severe neurodevelopmental syndrome and developmental ciliopathies resulting in oral-facial digital syndromes [8,14]. Analysis of the Cancer Genome Atlas has also revealed an increase in nonsynonymous mutations to the Integrator subunits in primary tumour samples [12,15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations